Frequency of EGFR Mutation and EML4-ALK fusion gene in Arab Patients with Adenocarcinoma of the Lung - Shafik Hanan Ezzat; Ashour Mohamed (Forum of Clinical Oncology, 2015)
Introduction: Improvement in the clinical outcome of lung cancer is likely to be achieved by identification of the molecular events that underlie its pathogenesis.